2016
DOI: 10.3233/nha-160008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary olive oil induces cannabinoid CB2 receptor expression in adipose tissue of ApcMin/+ transgenic mice

Abstract: BACKGROUND: Cannabinoid- 2 (CB2) receptor is known for its anti-obesity effects silencing the activated immune cells that are key drivers of metabolic syndrome and inflammation. Nutritional interventions in experimental models of carcinogenesis have been demonstrated to modulate tissue inflammation state and proliferation.OBJECTIVE: Aim of this study was to test, in ApcMin/+ mice, whether a diet enriched with olive oil, omega- 3 and omega-6- PUFAs affects the adipose tissue inflammation status.METHODS: Four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The previously cited study by Di Francesco et al [ 108 ] also did not find a significant impact of EVOO, OHT and OPE on CB2 expression. The only evidence of EVOO-dependent CB2 expression modulation comes from a single in vivo study, published in 2016 by Notarnicola et al [ 112 ]. Researchers treated C57BL/6J Apc Min/+ mice (a model for experimental colorectal carcinogenesis; mice with this mutation are predisposed to the development of multiple intestinal adenomas) with different FA-enriched diets for a period of 10 weeks.…”
Section: Dietary Active Principles With Ecs-mediated Effectsmentioning
confidence: 99%
“…The previously cited study by Di Francesco et al [ 108 ] also did not find a significant impact of EVOO, OHT and OPE on CB2 expression. The only evidence of EVOO-dependent CB2 expression modulation comes from a single in vivo study, published in 2016 by Notarnicola et al [ 112 ]. Researchers treated C57BL/6J Apc Min/+ mice (a model for experimental colorectal carcinogenesis; mice with this mutation are predisposed to the development of multiple intestinal adenomas) with different FA-enriched diets for a period of 10 weeks.…”
Section: Dietary Active Principles With Ecs-mediated Effectsmentioning
confidence: 99%
“…Regarding the role of CB2 in energy metabolism, its role as a pro-or anti-inflammatory in the central and peripheral tissues is controversial (Ueda et al, 2007;Deveaux et al, 2009;Chiurchiu et al, 2014;Maccarrone et al, 2015;Verty et al, 2015). Studies have reported a CB2 anti-obesity effect by silencing the activated immune cells in mice adipose tissue (Verty et al, 2015;Notarnicola et al, 2016), as well as a diet enriched with olive oil as responsible for increasing CB2 receptor expression in this tissue (Notarnicola et al, 2016).…”
Section: Endocannabinoid System and The Neuroendocrine Regulation Of Energy Metabolism Endocannabinoid System And The Hypothalamus -Adipomentioning
confidence: 99%
“…On the other hand, Rossi et al (2016) suggested that CB2 activation has anti-obesity effects, since the CB2 blockage increases fat store and reduces browning in human adipocytes. Furthermore, studies have reported a CB2 anti-obesity effect by silencing the activated immune cells in mice adipose tissue (Verty et al, 2015;Notarnicola et al, 2016).…”
Section: Endocannabinoid System and Weight Lossmentioning
confidence: 99%
“…In animal models of colorectal carcinogenesis, a diet based on olive oil, ω-3-/ω-6 fatty acids, showed antiobesity and anti-inflammatory activity through the interaction with CB2Rs, helping adipogenic homeostasis and decreasing endocannabinoid activation [ 330 , 331 ].…”
Section: Endocannabinoid Tone Modulation By Plant Flavonoidsmentioning
confidence: 99%